THE ROLE OF TECHNICAL VOCATIONAL EDUCATION AND TRAINING IN HUMAN DEVELOPMENT: PAKISTAN AS A REFERENCE POINT - Alam, Noor (European Scientific Journal, ESJ, 2015)
The improvement in Human Development (HD) is imperative for economic development of a country hence, a prudent government assigns priority to HD in its policy formulation and ensures availability of appropriate funding for this purpose. One of the important component of HD is the technical vocational education and training (TVET) that is gaining tremendous popularity in recent literature. The literature refers this subject to education and training that prepares people for an employment and makes them more productive in various economic fields. This paper analyzes the role of TVET in human development with reference to Pakistan. The findings reveal that the performance of TVET in Pakistan is not much satisfactory therefore its development sector is facing severe skills gap. There is an immediate need of reforms in education system with reference to development of skilled manpower in Pakistan.